The Employee Time Discipline Monitoring System based on Fingerprint Sensor and Website - ARDI, RIZKI (Universitas Andalas, 2023)
The problem of time discipline in the work environment is a common challenge that is often faced, especially in organizations with many employees. This problem becomes increasingly complicated when the organization has many employees with different work schedules and is spread across prominent locations. A time discipline monitoring system has been developed to overcome this problem. This system is designed to make monitoring employee attendance and time discipline easier by utilizing fingerprint scanner technology near the entrance to a room or office building. When an employee enters or leaves, they are required to scan their fingerprints using the fingerprint scanner. The data from the fingerprint scan is then recorded and stored on a server connected to the system. The administrator can easily access this data via a website provided by the system. This way, monitoring employee time discipline becomes more efficient. Furthermore, this system also has a feature that allows the head of organization to permit employees to have tasks outside the office. This simplifies the process of managing tasks outside the office and increases work flexibility. Based on the test results, the system demonstrates strong performance in monitoring, achieving a fingerprint detection accuracy of 95% and achieving a 100% success rate in website monitoring